2007
DOI: 10.1242/jcs.010686
|View full text |Cite
|
Sign up to set email alerts
|

Dynamin 2 mediates fluid-phase micropinocytosis in epithelial cells

Abstract: It is well-known that dynamin 2 (Dyn2) participates in clathrin- and caveolae-mediated endocytosis; however, the role of Dyn2 in coat-independent endocytic processes remains controversial. Here we demonstrate a role for specific spliced variants of Dyn2 in the micropinocytosis of fluid in epithelial cells, independent of coat-mediated endocytic pathways. A general inhibition of Dyn2 was first performed using either microinjection of anti-dynamin antibodies or Dyn2-siRNA treatment. Both of these methods resulte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
99
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(106 citation statements)
references
References 36 publications
5
99
0
Order By: Relevance
“…Others have reported that dominant-negative mutants of dynamin do not inhibit adenovirus-stimulated macropinocytosis (Meier et al, 2002) or vaccinia-virus induced macropinocytosis (Mercer and Helenius, 2008) and that microinjection of Dyn2 antibodies or siRNA depletion of Dyn2 does not inhibit EGF-stimulated macropinocytosis (Cao et al, 2007). In contrast, and consistent with our findings, overexpression of dominant-negative Dyn2 was previously shown to inhibit PDGF-stimulated macropinocytosis in Rat1 cells (Schlunk et al, 2004).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Others have reported that dominant-negative mutants of dynamin do not inhibit adenovirus-stimulated macropinocytosis (Meier et al, 2002) or vaccinia-virus induced macropinocytosis (Mercer and Helenius, 2008) and that microinjection of Dyn2 antibodies or siRNA depletion of Dyn2 does not inhibit EGF-stimulated macropinocytosis (Cao et al, 2007). In contrast, and consistent with our findings, overexpression of dominant-negative Dyn2 was previously shown to inhibit PDGF-stimulated macropinocytosis in Rat1 cells (Schlunk et al, 2004).…”
Section: Discussionsupporting
confidence: 89%
“…Macropinocytosis, which is induced upon stimulation by growth factors, involves the actin-driven formation of membrane protrusions that engulf large volumes of fluids. There are conflicting reports as to a role for dynamin in macropinocytosis (Meier et al, 2002; Schlunk et al, 2004;Cao et al, 2007). Macropinocytosis in our Dyn2 KO cells can be triggered by stimulation with PDGF, resulting in a transient, sixfold, increase in fluid phase uptake ( Figure 6A, PDGF).…”
mentioning
confidence: 71%
“…Assays for Internalization of Dextran and Transferrin, Pulse Labeling of Late Endosomal Compartments-Endocytosis of fluorescently conjugated transferrin or dextran was assayed as described previously (56).…”
Section: Methodsmentioning
confidence: 99%
“…However, the decay time constant of the average C m trace was much slower in KO cells (τ = 4.3 s, n = 14) than in control cells (τ = 2.7 s, n = 15) ( Figure 6F). Given the critical role of dynamin 2 in multiple forms of endocytosis in nonneuronal cells (32,45,54,58), it is surprising that the membrane retrieval was not blocked by the depletion of dynamin 2, an abundant dynamin isoform in β cells, indicating the presence of dynamin 2 independent endocytosis in these cells.…”
Section: And E)mentioning
confidence: 99%